From the Bench to the Screen: The Woman Judge in Film - Ray, Laura Krugman (2012)
Although there has been a dramatic increase in the number of women judges over the past half century, their cinematic counterparts have failed to reflect that change. This Article explores the paradoxical relationship between social reality and its representation on screen to identify a lingering resistance to the idea of women exercising judicial power. The Article first examines the sparse history of women judges as central characters in films of the 1930s, finding the tension in those films between judicial authority and domestic happiness. It then turns to Hollywood’s romantic comedies of the 1940s, which resolved that tension through the courtship of women judges by charming and tolerant suitors. Finally, the Article contrasts those films with the recent, darker films which present aspiring and active women judges struggling unsuccessfully to reconcile their professional and personal identities. All of these films use the woman judge as a vivid proxy for the broader theme of a woman challenging her traditional feminine role by assuming a position of authority; a sampling of recent films from countries with civil law systems reveals that American filmmakers have not been alone in exploring that theme with an eye to its difficulties rather than its rewards. All of these films, American and foreign, vintage and modern, suggest that the reality of women on the bench has yet to eliminate an element of discomfort with the idea of a woman successfully combining judicial power with a traditional and satisfying personal life